Population densities of Hylobates agilis in forests with different disturbance histories in Ulu Muda Forest Reserve, Malaysia. Issue 7 (6th May 2022) - Pang, Yi Heng; Lappan, Susan; Bartlett, Thad Q.; Mohd Sah, Shahrul Anuar; N. Rosely, Nik Fadzly; Ruppert, Nadine
Abstract: Small ape habitat throughout Malaysia is rapidly being lost, degraded, and fragmented, and the effects of these changes on the abundance on this taxon are currently unknown. This study assessed the group density of Hylobates agilis in virgin forest, previously logged forest (1960s–1990s), and recently logged forest (2015–2017) of the Ulu Muda Forest Reserve (UMFR), Kedah, Malaysia. We conducted fixed‐point active acoustic triangulation at nine survey areas to estimate group density. We used vegetation "speed plots" and satellite imagery to quantify habitat characteristics and used model selection to identify ecological predictors of group density variation. The estimated group density of H. agilis in UMFR was 4.03 ± 0.14 groups km −2, with an estimated total of 2927 ± 102 groups in areas below 450 m a.s.l. in UMFR. Group density did not differ significantly among habitat types. The best ecological predictors for group density were canopy cover and proportion of deforested area. Areas with recent deforestation were associated with relatively high group densities, suggesting compression of the populations persisting in these habitat types. The consistently high group densities detected in all forest types emphasizes the importance of degraded forest as habitat for H. agilis . Because of the threats to small apes in Malaysia, and the uncertain status of most populations, we recommend a nationwide population census and regular monitoring to inform conservation planning and implementation. Most urgently, we call for immediate and permanent protection of UMFR and other forests in the Greater Ulu Muda landscape to protect the globally significant populations of H. agilis, as well as other charismatic and threatened megafauna, birds, and flora in the area. Abstract : We estimated group density of agile gibbons (Hylobates agilis) in Ulu Muda Forest Reserve, Malaysia at 4.03 ± 0.14 groups km −2, with an estimated total of 2927 ± 102 groups in areas below 450 m a.s.l. Group density did not differ significantly among habitat types. The best ecological predictors for group density were canopy cover and proportion of deforested area. Highlights: This study estimates the population density of Hylobates agilis in Ulu Muda Forest Reserve, part of the largest remaining habitat for the species in mainland Asia. We estimate that lowland forests (<450 m a.s.l.) in Ulu Muda support 2972 ± 102 groups of H. agilis . Our data suggest that recently selectively logged forests support gibbon densities equal to those in undisturbed forest, demonstrating the importance of this landscape.